An integrated income and management model for internationalization - Carlos Silverio Huerta Jiménez; Marco Velázquez Albo (Universidade Estadual de Campinas, 2022)
Since its conception almost three decades ago, internationalization of higher education has seen the development of organization models for internationalization at institutional level. However, based on a literature analysis of the most cited models, what remains to be developed are institutional funding frameworks to support internationalization activities. This article proposes a model for the acquisition and management of funds for the internationalization of higher education institutions. It has the premise that an institutional integrative system can generate more resources than one that is not institutionally integrative. A strategic application of the model is discussed as an example for its application at institutional level. This model provides practical implications for strengthening internationalization efforts at higher education institutions.